UNDERSTANDING BUYA HAMKA DAN TAFSR AL-AZHAR - Puspitasari , Ria; Zamroji, M (LPPM IAI Hasanuddin Pare-Kediri, 2024)
Buya Hamka is a Multi-Talented figure of the archipelago who left many written works, in addition to being a scholar, writer, preacher, and politician. Throughout his life he always fought for an ideology based on tawhid teachings. The name HAMKA is an abbreviation of his name, namely H. Abdul Malik Karim Amrullah, author of the book of tafsir Al-Azhar which is his phenomenal work. The purpose of this study is to find out how Hamka's biography started from childhood to successfully create his phenomenal works, especially the book of tafsir Al-Azhar. The method used in this study is the library research method by collecting various information and data from various relevant sources. So, Buya Hamka is a Nusantara scholar who is known for his works with one of his phenomenal works, namely the book of tafsir Al-Azhar. Buya Hamka has also served as chairman of MUI and is known as a leader of Muhammadiyah.